Drug utilization study in Cardiology outpatient department at a tertiary care hospital - Slathia, Indu; Jadhav, Pradeep R.; Deb, Pooja; Verma, Shashwat (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Cardiovascular diseases are the most frequent cause of morbidity and mortality throughout the world particularly in South Asian population. With advent of newer, highly efficacious heterogeneous drugs and changing treatment guidelines, there’s a need to identify the cardiologist preference and prescribing patterns for rational utilization. Methods: It was an open label, prospective, cross-sectional, descriptive type of study conducted in Cardiology Outpatients at a Tertiary care hospital, Navi Mumbai. The study included 100 patients suffering from cardiovascular diseases attending cardiology outpatient department from October 2016 to March 2017. Informed consent was obtained and the currently prescribed drug details were recorded from prescription. The data was analysed for WHO core prescribing indicators and different types of drugs prescribed. Results: The average number of drug products prescribed was 3.4. Most commonly prescribed drugs were Antiplatelets (23%) followed by Statins (19.71%), β blockers (16%), Nitrates (11.70%), Angiotensin converting enzyme inhibitors (8.03%), Calcium channel blockers (5.50%), Angiotensin receptor blockers (4.70%), Diuretics (2.55%), Anticoagulant (1.83%), α+β blocker (1.46%), Cardiac glycosides ((1.09%), Potassium sparing diuretic and central sympatholytics. Majority of drugs were prescribed as single drugs (79.88%) while 20.11% as fixed dose combination (FDC). The combination of Telmisartan + Hydrochlorthiazide was the commonest prescribed FDC. Majority drugs were prescribed from NEDL 2015, but documented low generic prescribing. Conclusions: Antiplatelet and Statins dominated the prescribing pattern with high prescribing trend from national essential drug list, but showed scope for improvement in encouraging the cardiologist to prescribe by generic name.